The Urgency of Educational Management Information Systems (EMIS) in Managing Educational Data and Information - Della Dhienytha Oktavia; Dwi Meli Noviani (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
In the era of globalization, information systems play a crucial role in supporting the success of organizations, including educational institutions. Educational management information systems (SIMDIK) have become a primary necessity for managing data and information efficiently, replacing less effective manual methods. SIMDIK functions to collect, process, and disseminate information, thereby assisting educational institutions in planning and carrying out activities aligned with their vision, mission, and objectives to achieve quality education. This paper explores the basic concepts of information and information systems, including the relationship between facts, data, and information as the fundamental components of an information system. An information system is defined as a collection of components involving people, procedures, and data processing tools, both manual and electronic, working together to produce valuable information. By understanding these fundamentals, readers are expected to more easily comprehend the importance of SIMDIK in the field of education.